Isolation and Screening of Î± glucosidase Enzyme Inhibitor Producing Marine Actinobacteria Isolated from Pichavaram Mangrove - K Sathiyaseelan, Dr (International Journal of Pharmaceutical & Biological Archive, 2012)
Isolation and Screening of Î± glucosidase Enzyme Inhibitor Producing Marine Actinobacteria Isolated from Pichavaram Mangrove